EFEKTIVITAS JIGSAW METHOD PADA PEMBELAJARAN DARING MELALUI FORUM DISKUSI ZOOM DI FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - fathanaya, Harris; Siregar, Siti Masliana; Yulfi, Hemma; Irma, Fani Ade (Universitas Ciputra Surabaya, 2024)
ABSTRACT During the Coronavirus Disease-2019 (COVID-19) pandemic, the education sector must adapt by switching from face-to-face teaching and learning activities to online. There are various kinds of learning methods used, Many options are switching from teacher-based learning methods to student-based learning, one of them is the jigsaw method. The jigsaw method is considered to be able to trigger cooperative nature towards others and can increase understanding of the lecture materials or issues raised. To find out how the jigsaw method affects online learning through the Zoom discussion forum. This research is an experimental study with pre-test and post-test control group design in physiology class at Faculty of Medicine, University of Muhammadiyah North Sumatra. Data analysis was conducted using SPSS with Mann Whitney test. Which will be used to determine the effectiveness of the jigsaw method in online learning through zoom application. Subjects were 180 students with 90 students in Class A (conventional method) and 90 students in Class B (jigsaw method). There was a greater increase in the mean value of pre-test (56.22) and post-test (79.44) in the jigsaw method class, compared to the mean value of pre-test (30.22) and post-test (54.67) in the conventional class. In this study, the results of the pre-test and post-test on the jigsaw class method were considered more effective than the control class on the Mann-Whitney test with p<0.001. The jigsaw method is proven to be more effective when applied to online learning than conventional learning methods.